2020 46th Euromicro Conference on Software Engineering and Advanced Applications (SEAA) 2020
DOI: 10.1109/seaa51224.2020.00021
|View full text |Cite
|
Sign up to set email alerts
|

A Data-Driven Approach to Measure the Usability of Web APIs

Abstract: Application Programming Interfaces (APIs) are means of communication between applications, hence they can be seen as user interfaces, just with different kind of users, i.e., software or computers. However, the very first consumers of the APIs are humans, namely programmers. Based on the available documentation and the "ease of use" perception (sometimes led by corporate decisions and/or restrictions) they decide to use or not a specific API. In this paper, we propose a data-driven approach to measure web API … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…Few works build their analysis on WAPI usage logs comprised by the URL requests made to the WAPI [11], [2], [19]. Thus, not only these logs' potential is still unrevealed, but even quality issues related to them or their pre-processing and preparation have not gained the deserved attention.…”
Section: Related Workmentioning
confidence: 99%
See 3 more Smart Citations
“…Few works build their analysis on WAPI usage logs comprised by the URL requests made to the WAPI [11], [2], [19]. Thus, not only these logs' potential is still unrevealed, but even quality issues related to them or their pre-processing and preparation have not gained the deserved attention.…”
Section: Related Workmentioning
confidence: 99%
“…They reported that the results of their methods were impeded from the incomplete and noisy nature of these log data. In our previous paper [2], we proposed an approach to measure the usability of WAPIs by analyzing the usage logs generated during the development phase of consumers' application. We described the pre-processing steps of WAPI usage logs in general, and then demonstrated how we dealt with specific obstacles in the log data from the case study (e.g., data structuring, generalization).…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…But how much are these logs used and analyzed, beyond the typical traffic monitoring? Several works [8,2] suggest analyzing development logs to measure the usability of WAPIs and thus perform changes that increase the perceived usability from consumers point of view. In addition, there are various WAPI monitoring tools available that take as input the WAPI usage logs, but they are mostly oriented toward providing reporting dashboards or automatic alerting in case of WAPI failure [10].…”
Section: Introductionmentioning
confidence: 99%